Design optimization of integrated rotational inductor for high-speed AC drive applications - Khowja, M. Raza; Gerada, C.; Vakil, Gaurang; Patel, Chintanbai; Wheeler, Patrick (2017)
In order to make an efficient and power dense overall system, a close physical and functional integration of passive components is required instead of having a separate sub¬system for passives. Such power dense system is vital in aerospace and marine applications. This paper presents the design optimization of integrated rotational inductors for high speed AC drive applications. Design degrees of freedom like slot-pole combinations along with different winding configurations such as, single layer (SL), double layer (DL), concentrated winding (CW) and distributed winding (DW) are considered. In this paper, the rotational inductors are optimized for these degrees of freedom and compared with a benchmark EE core inductor in terms of total losses, weight and AC copper resistance at both fundamental frequency (1 kHz) and switching frequency (10, 15 and 20 kHz). The comparative analysis between EE core and rotational inductors has shown a significant reduction in total losses and AC copper resistance at fundamental frequency and all switching frequencies. In comparison with EE core inductor, 12 slots 2 poles rotational inductor with SL DW gives lowest total losses at fundamental frequency whereas 6 slots 2 poles rotational inductor with SL DW offers the lowest AC copper resistance at both fundamental and all switching frequencies.